2023
DOI: 10.20517/evcna.2023.01
|View full text |Cite
|
Sign up to set email alerts
|

Theranostic extracellular vesicles: a concise review of current imaging technologies and labeling strategies

Abstract: Extracellular vesicles (EVs), or exosomes, are naturally occurring nano- and micro-sized membrane vesicles playing an essential role in cell-to-cell communication. There is a recent increasing interest in harnessing the therapeutic potential of these natural nanoparticles to develop cell-free regenerative medicine and manufacture highly biocompatible and targeted drug and gene delivery vectors, amongst other applications. In the context of developing novel and effective EV-based therapy, imaging tools are of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 115 publications
0
3
0
Order By: Relevance
“…Recent advances in the therapy of ocular diseases based on MSC-EVs are demonstrated, and the associated challenges and prospects are discussed as well. Shinge et al (2022) presented an overview of the identified roles of plant exosome-like nanovesicles (PELNVs) in physiology and pathology [11] . They also provided new insight toward the engineering of the plant-originated EV for effective therapeutics besides the bacteria and mammalian cell, pointing out a clue for future direction to the ongoing research gaps.…”
Section: Article Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in the therapy of ocular diseases based on MSC-EVs are demonstrated, and the associated challenges and prospects are discussed as well. Shinge et al (2022) presented an overview of the identified roles of plant exosome-like nanovesicles (PELNVs) in physiology and pathology [11] . They also provided new insight toward the engineering of the plant-originated EV for effective therapeutics besides the bacteria and mammalian cell, pointing out a clue for future direction to the ongoing research gaps.…”
Section: Article Descriptionmentioning
confidence: 99%
“…The final review article by Aafreen et al (2023) introduces recent efforts and knowledge advances in EVbased therapies [12] . They also outline currently available labeling strategies by which EVs can be combined with various imaging agents and/or therapeutic drugs and genes.…”
Section: Article Descriptionmentioning
confidence: 99%
“…Exosome biogenesis is of particular interest as these sEVs have emerged as pivotal mediators for orchestrating intercellular signalling in physiological and pathological states 8,9 . Clinically, sEVs have gained signi cant importance in terms of theranostics [10][11][12][13] . Cancer cells employ exosomes to promote malignancy, and can be used as biomarkers, while stem cells utilize exosomes for regenerative functions 10,14 .…”
Section: Introductionmentioning
confidence: 99%